2021
DOI: 10.3390/ijms22168435
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Photoperiod on Necrosis Development, Photosynthetic Efficiency and ‘Green Islands’ Formation in Brassica juncea Infected with Alternaria brassicicola

Abstract: The main goal of growing plants under various photoperiods is to optimize photosynthesis for using the effect of day length that often acts on plants in combination with biotic and/or abiotic stresses. In this study, Brassica juncea plants were grown under four different day-length regimes, namely., 8 h day/16 h night, 12 h day/12 h night, 16 h day/8 h night, and continuous light, and were infected with a necrotrophic fungus Alternaria brassicicola. The development of necroses on B. juncea leaves was strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
4
6
0
Order By: Relevance
“…Meanwhile, reducing the input of carbon resources that support FHB development and mycotoxin production could provide new solutions for sustainable management of the disease. Photoperiod was reported as an important environmental factor that may impact the biological characteristics of phytopathogens, as well as their pathogenesis (Costa et al, 2021;Macioszek et al, 2021). In the present study, we found that alternating 8-h light and 16-h cycles dark was conducive to the growth of F. avenaceum Charlie 779 mycelia, and full darkness facilitated its conidia germination.…”
Section: Discussionsupporting
confidence: 60%
“…Meanwhile, reducing the input of carbon resources that support FHB development and mycotoxin production could provide new solutions for sustainable management of the disease. Photoperiod was reported as an important environmental factor that may impact the biological characteristics of phytopathogens, as well as their pathogenesis (Costa et al, 2021;Macioszek et al, 2021). In the present study, we found that alternating 8-h light and 16-h cycles dark was conducive to the growth of F. avenaceum Charlie 779 mycelia, and full darkness facilitated its conidia germination.…”
Section: Discussionsupporting
confidence: 60%
“…10). The same results have been previously described by Macioszek et al [121]. Moreover, electron microscopic analyses of pepper leaves infected with A. alternata spores showed anatomical changes with severe damage in chloroplasts, abnormal enlarged plastoglobuli and starch grains and thylakoids degradation compared to the control leaves (Fig.…”
Section: Light and Transmission Electron Microscopy (Tem)supporting
confidence: 90%
“…Elsanta) plants inoculated with B. cinerea developed stronger disease symptoms, if plants were transferred to darkness after infection compared to plants kept under their normal light conditions ( Meng et al, 2020 ). Macioszek et al (2021) observed that growth under short-day conditions results in increased necrosis formation in Brassica juncea plants infected with the necrotrophic fungus Alternaria brassicicola .…”
Section: The Photoperiod Influences Responses To Abiotic and Biotic Stressesmentioning
confidence: 99%